Predictors, Prognosis, and Management of New Clinically Important Atrial Fibrillation After Noncardiac Surgery: A Prospective Cohort Study. Issue 5 (October 2017) - Alonso-Coello, P.; Cook, D.; Xu, S. C.; Sigamani, A.; Berwanger, O.; Sivakumaran, S.; Yang, H.; Xavier, D.; Martinez, L. X.; Ibarra, P.; Rao-Melacini, P.; Pogue, J.; et al.
Abstract : (Abstracted from Anesth Analg, 125(1):162–169, 2017) The purpose of the POISE (PeriOperative ISchemic Evaluation) trial substudy has multiple objectives: it aims to deduce the associations between new clinically important atrial fibrillation (AF) and patient outcomes, as well as patient management strategies, while identifying a valid clinical prediction model for new clinically important AF in patients undergoing noncardiac surgery.